Pomponazzi’s De fato and Thomas Aquinas - Dagron, Tristan (Verbum – Analecta Neolatina, 2004)
In his De fato, written in 1520, Pomponazzi examines Thomas Aquinas’s doctrine of predestination. From his point of view, Thomas’s solution to the traditional conflict between divine science and human liberty is twofold: it mixes philosophy and theology, thereby transforming the revealed doctrine as well as that of philosophical rationality. The analysis of the Thomistic position is therefore an opportunity to define the specificity of the theological discourse from a critical point of view.